Olmsted Syndrome - Elise Tonoli, Renata (Hindawi Publishing Corporation, 2012)
Olmsted syndrome is a rare congenital, sharply circumscribed transgredient palmoplantar keratoderma. It was first described by Olmsted in 1927. The diagnosis of this rare disease depends on clinical features like symmetrical involvement of keratoderma of the palms and soles and the symmetrical hyperkeratotic plaques around the body orifices. It starts in the neonatal period or in childhood. The disease has a slow but progressive and extremely disabling course. Treatment of Olmsted syndrome is often based on topical therapy with retinoic acid, corticosteroid, emollients, and keratolytics. The present paper describes a case of Olmsted syndrome and its treatment.